Weak Connection Regulation Technology for Source-Storage-Load Collaborative Microgrids Based on Direct Power Control - Peng REN; Zhigang ZHAO; Hongchao GAO; Wu WEN; Yingyi JIANG (Zhongguo dianli)
The development of distributed energy has transformed buildings into new energy complexes integrating generation, storage, and consumption. However, the fluctuation and randomness of photovoltaic power generation and equipment power consumption leads to the grid and regional supply and demand imbalance. So it is necessary to optimize the configuration of the regional source-storage-grid-load to enhance the efficiency of the regional power consumption and tap into the adjustable potential, achieving fast response and regulation. This paper built a user-side source-storage-grid-load DC power supply system, analyzed the characteristics of each device of the system, proposed a power direct-control flexible regulation algorithm, and conducted verification in the PV future houses of Zhuhai Gree Electric Appliances. The paper also studied the regional DC power supply and flexible regulation technology, analyzed the flexible characteristics of air conditioners, energy storage, photovoltaic, etc., and verified the power direct-control flexible regulation algorithm and evaluation indexes. From the effect of testing and verification, the whole system enables real-time response and rapid adjustment, thus improving the energy utilization efficiency, reducing the grid-side quota and realizing the local consumption of PV.